The future of wellness tourism after COVID-19 - Piatto Clerici, Andressa; Murphy, Catriona; Castanheira Almeida, Nuno Miguel (European Spatial Research and Policy, 2023)
The tourism industry has drastically reduced its activity since the emergence of the COVID-19 pandemic, yet there has been an undeniable rise in demand for wellness tourism which now represents one of the fastest growing tourism market segments globally. Admittedly, while the COVID-19 pandemic has delayed the forecasted wellness tourism growth trend, this segment has stood fast at USD 4.4 trillion in 2020 while global GDP declined by 2.8%. In 2020, the wellness tourism market was valued at USD 436 billion, projected to rise to USD 816 billion by 2022 with more than 1.2 billion trips being realised and anticipated growth estimated at USD 1.0 trillion by 2025. The main purpose of this study is to ascertain the future trends of wellness tourism, and to investigate the extent to which this upward growth trend can be sustainably maintained post COVID-19. A qualitative structured interview methodology was employed using email interviews comprising six pre-determined questions with three expert wellness tourism participants. These expert interviewees were based in countries that were severely impacted by COVID-19, namely Brazil, USA, and Portugal. NVivo Nudist was used to analyse the primary data collected. In validating previous research findings, this study indicates that despite the challenges facing the sector, upward growth patterns in wellness tourism will continue beyond the COVID-19 pandemic.